Self-administered mindfulness interventions reduce stress in a large, randomized controlled multi-site study - ALESSANDRO SPARACIO (Nature Human Behaviour, 2024)
Mindfulness witnessed a substantial popularity surge in the past decade, especially as digitally self-administered interventions became available at relatively low costs. Yet, it is uncertain whether they effectively help reduce stress. In a preregistered (OSF https://doi.org/10.17605/OSF.IO/UF4JZ; retrospective registration at ClinicalTrials.gov NCT06308744) multi-site study (nsites = 37, nparticipants = 2,239, 70.4% women, Mage = 22.4, s.d.age = 10.1, all fluent English speakers), we experimentally tested whether four single, standalone mindfulness exercises effectively reduced stress, using Bayesian mixed-effects models. All exercises proved to be more efficacious than the active control. We observed a mean difference of 0.27 (d = −0.56; 95% confidence interval, −0.43 to −0.69) between the control condition (M = 1.95, s.d. = 0.50) and the condition with the largest stress reduction (body scan: M = 1.68, s.d. = 0.46). Our findings suggest that mindfulness may be beneficial for reducing self-reported short-term stress for English speakers from higher-income countries.